Abdusshamad al-Palembani; His Thoughts and Movements in the Spread of Islam in Indonesia - Wahyudi Buska; Yogia Prihartini; Ali Muzakir (AL-FIKRA, 2020)
This study aims to find the thoughts and movements carried out by Abdusshamad al-Palimbani. The method used in this research is a literature study or library research, by combining activities related to library data collection methods, reading, collecting, and processing research materials consisting of books, manuscripts, hand scripts. The results of the research showed that Abdusshamad al-Palimbani had broad ideas to build Muslim communities, especially in South Sumatra and generally in the archipelago in the areas of Sufism, Tawhid and important to defend the State. In the teachings of Abdusshamad al-Palimbani to his students and the works left behind his mind can be known. His thoughts were collected in various works;(a) Hidayatus Salikin fi Suluk Maslak al-Muttaqiin, (b) Siyarus Salikin ila Ibadat rabb al-alamin (c) Thufah Al-Raghibin fi Bayan Haqiqat Faith Al-Mu'inin, (d). Nasihat al-Muslimin wa Tadzkirat alMu‟minin fi Fadha‟il Al-Jihad fi Sabilillah wa Karamat al-Mujahidin fi Sabilillah (e) Zuhrat al-Murid fi Bayan Kalimat al-Tawhid, (f) Al-Urwat al-Wutsqa wa Silsilat Uli al-Ittiqa, (g) Ratib Abdus Shamad, (h) Zadd Al-Muttaqin fi Tawhid Rabb al-Alamin. The spread of Islam is intended to encourage the community to always fill its days with remembrance and reverence; (a) protect yourself from the fire of hell (b) Allah favors you that God makes us out of those who call on His name, He does not make us blameless (c). be bright and open with the zikrullah light (d). to him, the windows of heaven were opened (e). gentle heart and khusyu’ (f). abolished it with one sentence from the remembrance of ten crimes.